2015
DOI: 10.1007/s10529-015-1827-z
|View full text |Cite
|
Sign up to set email alerts
|

Production of transgenic beef cattle rich in n-3 PUFAs by somatic cell nuclear transfer

Abstract: Our results demonstrated that the codon-optimized C. elegans mfat1 gene can be functionally expressed in the beef cattle and converts n-6 PUFAs to n-3 PUFAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…The introduction of the Fat-1 gene in mouse, pig, sheep, cattle, and cow resulted in high levels of n-3 PUFAs and significantly lower n-6/n-3 PUFA ratios in their tissues [10][11][12]23,46,47]. In our study, the same results were obtained by comparing n-6 and n-3 PUFA contents between 100-day transgenic fetuses and wild type fetuses.…”
Section: Discussionsupporting
confidence: 81%
“…The introduction of the Fat-1 gene in mouse, pig, sheep, cattle, and cow resulted in high levels of n-3 PUFAs and significantly lower n-6/n-3 PUFA ratios in their tissues [10][11][12]23,46,47]. In our study, the same results were obtained by comparing n-6 and n-3 PUFA contents between 100-day transgenic fetuses and wild type fetuses.…”
Section: Discussionsupporting
confidence: 81%
“…For example, feeding beef cattle with rumen‐protected fish oil supplements or oil seeds can be used to increase C20:5 n ‐3 and C22:6 n ‐3 concentrations. Also, there have been efforts to modulate the genetics of bovines to increase total n ‐3 FA: Cheng et al . demonstrated that the codon‐optimized C. elegans mfat1 gene can be functionally expressed in beef cattle and converts n ‐6 PUFAs to n ‐3 PUFAs.…”
Section: Ruminant Meat and Human Healthmentioning
confidence: 99%
“…However, the transgenic goats were unable to sustain the altered fatty acid ratios possibly due to instabilities of the transgene-derived mRNA. Enabling livestock with the endogenous production of omega-3 fatty acids, which are highly beneficial for human health and mainly available through the consumption of oily fish, provides a new, more sustainable food source for omega-3 fatty acids and was demonstrated in pigs, sheep and cattle (Lai et al 2006;Saeki et al 2004;Zhang et al 2013;Cheng et al 2015). Transgenic cattle,…”
Section: Transfer Of Early Concepts From Mouse To Livestockmentioning
confidence: 99%